(untitled) (Research, Society and Development, 2019)
Lately industries are facing major challenges in seeking to gain their place in the market and be able to maintain them, knowing how to use their failures to improve is a great advantage and can be used as a differential, the maintenance and production sectors. should be aligned to reduce the number of repeat occurrences. The present work presents a field study aiming to implement a failure analysis methodology in a low density polyethylene industry, thus reducing the negative impact caused by maintenance. The research is exploratory, quantitative and qualitative. A case study was conducted on addressing the use of analysis and problem solving tools, an example of how they are applied and the structure of the analysis process, the results from the application were optimistic and brought many opportunities for improvement in the industry. maintenance plans, thus emphasizing the importance of keeping records of occurrences and capturing fault information to generate improvements from their analysis. In the months following the implementation of the methodology, the results in the reduction of maintenance time in the period from July to October were noticeable, going from 51.07% to 55.15%, OEE improvement rate of 4.05, with a tendency that With each new analysis there are opportunities to improve processes and prevent the loss of OEE.